Facile preparation of monodispersed core/shell zinc oxide@polystyrene (ZnO@PS)nanoparticles via soapless seeded microemulsion polymerization - Liu, P.
Monodispersed core/shell zinc oxide@polystyrene (ZnO@PS)nanoparticles with chemical bonds between the inorganic core and the polymer shell were prepared successfully by the facile soapless microemulsion polymerization of styrene (St)with the oleic acid modified zinc oxide (OA-ZnO)nanoparticles as seeds, and potassium persulphate (KPS)as initiator in water. The products were characterized by elemental analysis (EA), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM)and thermogravimetric analysis (TGA). The mechanism of the nucleation was also mentioned. The ZnO@PS nanoparticles could be well-dispersed n water and the emulsion was found to be remarkably stable. Ultraviolet-visible (UV-vis)analysis showed that the composites had high absorption in the ultraviolet region and low absorption in the visible region.
Keywords: MONODISPERSED; CORE/SHELL; ZINC OXIDE@POLYSTYRENE; SOAPLESS SEEDED MICROEMULSION POLYMERIZATION; MECHANISM OF THE NUCLEATION